The relationship between work-life balance and employee retention among employees at Sarawak Energy Berhad (SEB), Kuching, Sarawak / Tara Jestina Jefri - Jefri, Tara Jestina (2019)
This study is to investigate the relationship between the three aspects of work-life balance (flexible working schedule, job burnout and job sharing) and employees’ retention. Work life balance is an important concept which affect every working person that wants to maintain equilibrium between their work life and personal life. This study was conducted at Sarawak Energy Berhad (SEB) Kuching, Sarawak. The design for this study is correlational. The sampling technique used is convenience. The study involved 86 respondents between executive and non-executive at Sarawak Energy Berhad (SEB) Kuching, Sarawak. Data were collected using a set of questionnaires that consists of 26 questions that are related to (flexible working schedule, job burnout, job sharing) towards employees’ retention. The data were analysed using SPSS Version 25. A conceptual framework was adopted from Azman, Ghani, Hashim and Sabri (2016). The result shows a positive relationship and significant correlation between job burnout and employees’ retention. Therefore, result of this finding shows that job burnout is the higher (0.397**, p>0.30) creator affecting the employees’ retention at Sarawak Energy Berhad (SEB) Kuching, Sarawak. The outcome of this study would help to increase the knowledge on work-life balance factors and employees’ retention. In addition, the result would also benefit the management of the organization assisting them in to reduce job burnout at the workplace. Lastly, the findings would help the employees to understand the feeling at the workplace. This study contributes to the need for knowledge and understanding work-life balance factors (flexible working schedule, job burnout, job sharing) and employees’ retention.